Diagenesis and hydrocarbon charging period in the Lower Cretaceous Bayingebi Formation, Hari sag, Yin`E Basin, Northern China. (1st February 2023) - Xing, Guangyuan; Qi, Kai; Ren, Zhanli; Cui, Junping; Zhang, Ying; Yang, Guilin
Abstract: The Lower Cretaceous Bayingebi Formation at the Hari sag, Northern China is a significant bearing oil-gas tight reservoir in the Yin`E Basin. In order to understand petrophysical properties of the reservoirs, the diagenesis and hydrocarbon accumulation phases were investigated using casting thin sections, scanning electron microscopy (SEM), X-ray diffraction and fluid inclusion analysis. Additionally, the histories of burial evolution, organic matter thermal evolution and hydrocarbon charge are investigated. The results showed that the pore types include primary pore, intergranular pore and dissolution intragranular pore. The diagenesis of sandstone reservoirs in the process of burial and diagenesis mainly includes compaction, fracture, cementation, metasomatism and dissolution. The comprehensive analysis of various diagenetic stage indexes shows that Bayingebi Formation is in the middle diagenetic stage A-B. The homogenization temperature and salinity of fluid inclusions are low temperature and low salinity (120 °C ∼ 130 °C, 0% ∼ 9%), medium temperature and high salinity (140 °C ∼ 150 °C, 10% ∼ 17%) and high temperature and medium salinity (160 °C ∼ 170 °C, 9% ∼ 11%) respectively. According to the homogenization temperature of the inclusions and the history of burial evolution, the Bayingebi Formation has mainly three phases of hydrocarbon accumulation (100 ∼ 97Ma, 93 ∼ 87Ma, 84 ∼ 81Ma).